Peaceful Montessori parenting : a guide to raising capable kids with joy, simplicity, and intention - Turner, Haley (Quarry, 2025)
"Peaceful Montessori Parenting is an accessible introduction to Montessori play-based learning at home, including both an introduction to the principles of Montessori education with an emphasis on home-based application as well as simple, budget-friendly projects and activities for hands-on engagement"--